The Role of Family Meeting In Dealing With Rejection Towards Hospital Discharge of Terminally Ill Cancer Patients - Witjaksono, Maria; Yatiningsih, Dwi; Widaretno, Hesti; Asdiniah, Rani; Ame, Ame (Indonesian Journal of Cancer, 2018)
Background: Rejection towards discharge planning of terminally ill patients and the role of family meetings to overcome such issue has not been evaluated. The aims of this study were to identify who and the reasons of rejection, to evaluate the effectiveness of family meetings, and to assess the important aspects in preparing homecare.Methods: This is an interventional study using queasy-experimental design. Samples of the study were family members of terminally ill patients who refused patient discharge from 1st of May to 31st of October 2016. Paired-Sample T-test was applied to analyze the result. Result: Rejections of discharge planning was mostly by the families. The most reason of rejection was lack of knowledge and skills in taking care of the terminally ill patients (40%). Family meetings solved the problem of rejection. The total score of 10 aspects needed in taking care of terminally ill patients was significantly increased (p=0.000). Conclusion: Family meetings effectively changed the attitude towards hospital discharged